EFEKTIVITAS PROGRAM CSR DALAM MEMBERDAYAKAN KOMUNITAS TULI GRESIK OLEH PT PERTAMINA GAS UNIT OPERATION EAST JAVA AREA - Agustina, Lailatul Wahdah (Universitas Negeri Surabaya, 2022)
Persons with Disabilities often experience discrimination in the fulfillment of their rights. The government's inability to guarantee the rights of Persons with Disabilities can be seen in the economic aspect. There are still a large number of workers with disabilities who do not get decent jobs due to their educational background. This study uses the Stimulus Organism Response Theory which is adapted to the Theory of Program Effectiveness according to (Sutrisno E., 2007). There are 5 indicators of effectiveness, namely Program Understanding, Right on Target, Right on Time, Achievement of Goals, and Real Change. This study aims to find out how big the level of effectiveness of the CSR Program in Empowering the Gresik Deaf Community by PT Pertamina Gas Operation Unit East Java Area is. This study used a quantitative approach. Data collection was carried out by distributing questionnaires to 26 members of the Gresik Deaf Community. The informants were selected based on the experience of the informants who participated in the CSR program, how they first knew about the CSR Program of PT Pertagas, gender, age, employment status, and the reasons why they consistently participated in the CSR Program of PT Pertagas. The results of this study found three dimensions to obtain the Very Effective category, namely Program Understanding with a TCR score of 83.97%, Right on Target with a TCR score of 86.53%, and the Achieving Goals dimension with a TCR score of 84.61%. While the other two dimensions are in the Effective category, namely the Punctuality dimension with a TCR score of 64.85% and Real Change with a TCR score of 75.00%. Keywords: Effectiveness, Corporate Social Responsibility, Stimulus Response Theory.